2002
DOI: 10.1101/gad.976002
|View full text |Cite
|
Sign up to set email alerts
|

Control of neuronal subtype identity by the C. elegans ARID protein CFI-1

Abstract: The Caenorhabditis elegans hermaphrodite nervous system is composed of 302 neurons that fall into at least 118 diverse classes. Here we describe cfi-1, a gene that contributes to the development of neuronal diversity. cfi-1 promotes appropriate differentiation of the URA sensory neurons and inhibits URA from expressing the male-specific CEM neuronal fate. The UNC-86 POU homeodomain protein is present in CEM and URA neurons, and can promote expression of CEM-specific genes in both CEM and URA, but CFI-1 inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 55 publications
4
75
0
1
Order By: Relevance
“…To determine whether the region of R09F10 identified was part of a protein-coding gene, we inspected the genomic sequence manually and assembled a putative gene structure. Using the polymerase chain reaction (PCR) and primers corresponding to the predicted gene, we were able to amplify a cDNA from a mixed-stage cDNA library we constructed 34 (S Shaham, unpublished data). The existence of a cDNA suggested that the region of R09F10 we identified indeed contained a transcribed gene, designated R09F10.9.…”
Section: Ced-13 Encodes a Conserved Bh3-only Proteinmentioning
confidence: 99%
“…To determine whether the region of R09F10 identified was part of a protein-coding gene, we inspected the genomic sequence manually and assembled a putative gene structure. Using the polymerase chain reaction (PCR) and primers corresponding to the predicted gene, we were able to amplify a cDNA from a mixed-stage cDNA library we constructed 34 (S Shaham, unpublished data). The existence of a cDNA suggested that the region of R09F10 we identified indeed contained a transcribed gene, designated R09F10.9.…”
Section: Ced-13 Encodes a Conserved Bh3-only Proteinmentioning
confidence: 99%
“…We also observed almost complete loss of GFP expression at the CEM positions in several other unc-86 loss-of-function mutants (Table 3). UNC-86 is expressed in 47 neurons during C. elegans development, including male CEMs and hermaphrodite HSNs (Finney and Ruvkun 1990), and is critical for the proper differentiation of these UNC-86-expressing neurons, including the differentiation and survival of CEM neurons in males (Finney et al 1988;Shaham and Bargmann 2002). Interestingly, the mouse ortholog of UNC-86, Brn3c, has been shown to act genetically upstream of the mouse BarH homeodomain protein Barhl1 to promote terminal differentiation and survival of mechanosensory hair cells (Li et al 2002), suggesting a conserved regulatory relationship between these two types of homeodomain proteins.…”
Section: Unc-86 Is Required For Cem Cell Fate Specification Independementioning
confidence: 99%
“…An ARID family TF CFI-1 (CEM neuron Fate Inhibition 1) binds to an AT rich region and is required for the CEM fate inhibition (Shaham and Bargmann 2002). However, cfi-1 is not required for pkd-2 expression in CEM neurons (Shaham and Bargmann 2002). Identifying the TFs that activate daf-19m, daf-19m direct targets, and PKD gene battery regulators will reveal how a cilium is specialized in form and function.…”
Section: Resultsmentioning
confidence: 99%
“…The CEM/IL2 enhancer sequences are AT enriched. An ARID family TF CFI-1 (CEM neuron Fate Inhibition 1) binds to an AT rich region and is required for the CEM fate inhibition (Shaham and Bargmann 2002). However, cfi-1 is not required for pkd-2 expression in CEM neurons (Shaham and Bargmann 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation